Kajian Strategi Pengembangan Usaha Industri Kripik Singkong Perusahaan PT Inti Sari Rasa di Bekasi - Praba Indariawati; Sapta Raharja; Soewarno T. Soekarto (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2011)
Cassava is one of local prime comodity in Indonesia. Crispy chips of cassava is one of product was made from cassava. People interest in developing of it, for example, people in Bekasi. PT Inti Sari Rasa was built in 1981, it has a business in crispy chips of cassava industry. The company have an internal and external constraints to develop and awaken crispy chips of cassava industry (increasing competition power of product and business).  The aims of the study are: (1) to identify and evaluate the internal factor business of crispy chips of cassava industry in PT. Inti Sari Rasa which is become strength and weakness factors; (2) to identify and evaluate the external factors which is become opportunities and threats that can influence its developing; (3) to analyze strategy which was applied and formulate the alternative strategy for developing business of crispy chips of cassava. Data which was used in this analysis covered  primary and secondary data which have quantitave and qualitative character. The respondents were : (a) company management (5 persons); (b) agent (10 agents); (c) consumer (50 persons). The tools analysis used matrix of IFE (Internal Factor Evaluation), EFE (External Factor Evaluation), IE (Internal – External) and SWOT (Strengths, Weaknesess, Opportunities and Threats) to arrange developing business strategy, also QSPM (Quantitative Strategic Planning Matrix) to determine priority strategy which was chose. The result of IFE matrix calculation got score 2.703 and EFE 2.511. Based market on the mapping by IE matrix, position of the company in the cell V. Strategy that can apply in this cell are market penetration and developing product and market. The result of SWOT matrix are four types of strategy that done, they are : S-O strategy, to maintain consumer’s loyalty and increasing productivity; W-O strategy, to expand distribution area and market, to increase quality of human resource marketing, to apply accountancy system in the company's finance; S-T strategy, to increase product diversification to counter a new comer, to increase image product in order to implant consumer loyalty; W-T strategy, to increase promotion activity in order to catch the potential consumer, to fix the product price in order to meet the most people. Based on the alternative strategy that was formulated. QSPM used to choose priority strategy which can be applied, it is expanding distribution area and market (4,612). That strategy rely on strengthens and opportunities, also solve some weaknesses and anticipate threatens which come from company surrounding